1994
DOI: 10.1111/j.1365-2044.1994.tb14236.x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of intra‐articular morphine after arthroscopic meniscectomy

Abstract: SummaryA study was performed to In conclusion, no significant differences in pain scores or in requirements for supplemental morphine were observed between patients receiving in tra-articular versus intramuscular morphine 2 rug after elective arthroscopic nieniscectonij. and consequently no specific local analgesic effect of iiitra-articular morphine could be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…1 Such imbalance may be of importance in several RCTs. 35,36,38,39,44,45,[48][49][50][51][52][53][54][55][56][57][58][59][60][61] All these trials, placebo controlled or not, had a group size below 20, which gives an OPVS item number 2 score of 0/3.…”
Section: Most Positive Trials Are Of Low Research Quality And/or Havementioning
confidence: 99%
See 1 more Smart Citation
“…1 Such imbalance may be of importance in several RCTs. 35,36,38,39,44,45,[48][49][50][51][52][53][54][55][56][57][58][59][60][61] All these trials, placebo controlled or not, had a group size below 20, which gives an OPVS item number 2 score of 0/3.…”
Section: Most Positive Trials Are Of Low Research Quality And/or Havementioning
confidence: 99%
“…93 Unfortunately, several studies did not include placebo groups. 40,49,51,54,81,[94][95][96][97][98] Trials without placebo control (Table 4) are often referred to as evidence for peripheral opioid analgesia. However, there is a lack of evidence from placebo-controlled trials, and the results need to be reviewed in the light of recent knowledge.…”
Section: Most Positive Trials Are Of Low Research Quality And/or Havementioning
confidence: 99%
“…(28) Presence of local anaesthetics may be a factor to inhibit neuronal mechanisms that are responsible for the effect of morphine. This may explain why some studies with regional or local anaesthesia have failed to show the effect of IA morphine, (29)(30)(31) whereas patients operated under general anaesthesia have demonstrated profound effect of IA morphine. (4,15,32,33) In the current study, spinal anasthesia with bupivacaine was applied.…”
Section: Discussionmentioning
confidence: 96%
“…The possibility that pain reduction and the decreased need of analgesics after IA morphine was secondary to a systemic effect was investigated by several authors who demonstrated that the IA was superior than the intravenous route in pain reduction and, in some cases, the intragroup difference did not achieve statistical significance. However, the superiority of the intravenous over the IA route was not demonstrated when similar doses were used 10,27,28 . It was also suggested that the effects of IA morphine were more prolonged that that of the intravenous administration.…”
Section: Discussionmentioning
confidence: 99%